Automated code remediation - Johnson, Pat; Kundzich, Olga; Schneider, Jonathan (Jonathan K.) (O'Reilly Media, Inc., 2023)
The software industrial revolution has arrived. There's an explosion of custom applications today, and we assemble them faster than ever from third-party and open source software. But as applications grow in complexity and vulnerabilities mount, updating software becomes a tedious, intractable part of a developer's job. When you fail to keep up, the software becomes less secure and harder to maintain and eventually stops working. This report explains how organizations can stay on top of software vulnerabilities and maintenance, freeing developers to focus on creating new solutions. The practice of automated code remediation is a next-generation code search and scanning technology that goes beyond search to fix issues automatically across the enterprise codebase. When you automate code refactoring and remediation, code quality and security improve. Developer experience is also enhanced, accelerating the impact your business can make.